The Transatlantic Trade and Investment Partnership, investor-state dispute settlement and China - Axel Berger; Lauge N. Skovgaard Poulsen (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
This Perspective argues that since China has been a strong proponent of investment arbitration for more than a decade, Beijing is likely to favor the mechanism in a future EU-China deal – irrespective of whether it is included in the Transatlantic Trade and Investment Partnership agreement.
Keywords: 330